1992
DOI: 10.1111/j.1365-2044.1992.tb02002.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of omeprazole and ranitidine for prophylaxis against aspiration pneumonitis in emergency Caesarean section

Abstract: SummaryOne hundred and sixty-two Chinese women undergoing emergency Caesarean section were allocated at random on admission to the labour ward to receive one of three regimens for orally administered chemoprophylaxis against acid aspiration: ranitidine 150 mg 6 hourly with sodium citrate at induction of anaesthesia, omeprazole 40 mg I2 hourly with sodium citrate. or omeprazole 40 mg 12 hourly alone. Intragastric pH and volume were measured immediately after induction of anaesthesia. Ten patients ( I 7%) in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…12,14 Only one study to date has compared ranitidine and omeprazole in labour. 15 This study concluded that although omeprazole has been shown to be more effective immediately before emergency caesarean section, this was not the case in labour where the gastric pH was lower in patients receiving omeprazole and sodium citrate (pH 5.67) compared to ranitidine and sodium citrate (pH 6.16). Although the results are statistically significant they are not clinically significant.…”
Section: Discussionmentioning
confidence: 90%
“…12,14 Only one study to date has compared ranitidine and omeprazole in labour. 15 This study concluded that although omeprazole has been shown to be more effective immediately before emergency caesarean section, this was not the case in labour where the gastric pH was lower in patients receiving omeprazole and sodium citrate (pH 5.67) compared to ranitidine and sodium citrate (pH 6.16). Although the results are statistically significant they are not clinically significant.…”
Section: Discussionmentioning
confidence: 90%
“…Of the 23 studies that were identified relating to the reduction of aspiration pneumonitis, 22 were included involving 2658 women (Dewan 1985; Elhakim 2005; Ewart 1990; Frank 1984;Hong 2004; Husemeyer 1980; Iqbal 2000; Jasson 1989; Lin 1996; Ormezzano 1990; Orr 1993; Ostheimer 1982; Ozkan 2000;Pickering 1980; Rocke 1994; Rout 1993; Tripathi 1995; Tryba 1983; Wig 1987; Yau 1992; Zoroglu 1999; Zue 1999). One study was put in section on ’Awaiting classification’ whilst we try to contact authors (Karamanlioglu 1995).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies (Ewart 1990; Lin 1996; Tripathi 1995; Yau 1992) compared H 2 antagonists with proton pump antagonists.…”
Section: Resultsmentioning
confidence: 99%
“…RCTs have shown that sodium citrate reduces acidity without affecting gastric volume, 34 that ranitidine combined with sodium citrate reduces gastric volume and increases pH, 35 that omeprazole also reduces the risk of aspiration 36 and that omeprazole results in higher mean pH than ranitidine, although ranitidine with sodium citrate is cheaper. [37][38][39] Nausea and vomiting may be provoked by hypotension during regional anaesthesia for caesarean section. Treatment of the cause will alleviate the symptom.…”
Section: Aspects Of Anaesthesia For Caesarean Sectionmentioning
confidence: 99%